EXTRACTION AND CHARACTERIZATION OF MUCILAGE FROM LEAVES OF Pereskia bleo (ROSE CACTUS) [Ekstraksi dan Karakterisasi Getah Daun Kaktus Mawar (Pereskia bleo)] - Ng Tze Hong; Nor Hayati Ibrahim (Jurnal Teknologi dan Industri Pangan, 2012)
Pereskia bleo (rose cactus) is a type of tropical herbs which has long been used for its medicinal benefits among Malays and is also known to contain complex polysaccharide called mucilage. In this study, mucilage from leaves of rose cactus was extracted by using distilled water or 0.14 M sodium hydroxide (NaOH) solution at three different temperatures (i.e. 50°C, 70°C or 90°C). There was a significant (p<0.05) interaction effect between type of medium used and temperature on yield of mucilage. Extraction using 0.14 M NaOH solution at 70°C provided the highest yield (2.55%) of mucilage as compared to other extraction conditions. The mucilage extracted with 0.14 M NaOH solution at 70°C was further characterized in terms of physicochemical properties and compared with arabic gum. The crude protein, moisture and ash content of the mucilage were 4.81%, 13.59% and 28.67% respectively. It possessed appreciable amount of elements such as calcium (48.96 mg/g sample), and potassium (15.58 mg/g sample). The pH value of the mucilage was 10.89 (alkaline) and it exhibited a clear thixotropic flow behavior with acceptable emulsion capacity (7.08%) and stability (7.31%) at 1% concentration. The colour of the mucilage and water holding capacity (WHC) was L*= 68.81, and 461.87 % respectively. These findings suggest that rose cactus mucilage could be an interesting functional food ingredient as it originated from a well-known medicinal plant though further study should be done in order to fully understand its potential as one of alternative food hydrocolloids.